A spatial nonparametric analysis of local multipliers - Stefano Magrini; Margherita Gerolimetto (European Regional Science Association (ERSA), 2011)
In this paper we present a spatial nonparametric analysis of local multipliers. Following Moretti (2010), we estimate the effect of an exogenous shock in the employment of the tradable sector on the employment in either the nontradable sector or the rest of the tradable sector using a nonparametric procedure that allows for spatial effects. In addition, due to its nonparametric nature, the adopted procedure is robust not only to possibly nonlinear functional forms but also to endogeneity in the regressors. Our analysis shows that the inclusion of spatial effects reveals the presence of a nonlinear relationship between tradable on nontradable.
Keywords: 330